2017
DOI: 10.1007/978-3-319-67308-0_61
|View full text |Cite
|
Sign up to set email alerts
|

Min-Max Regret Scheduling to Minimize the Total Weight of Late Jobs with Interval Uncertainty

Abstract: We study the single machine scheduling problem with the objective to minimize the total weight of late jobs. It is assumed that the processing times of jobs are not exactly known at the time when a complete schedule must be dispatched. Instead, only interval bounds for these parameters are given. In contrast to the stochastic optimization approach, we consider the problem of finding a robust schedule, which minimizes the maximum regret of a solution. Heuristic algorithm based on mixed-integer linear programmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…We have also shown that there may exist infinitely many worst-case scenarios. Another example of a min-max regret scheduling problem with the property that worst-case scenario is not always extreme is the minimization of the weighted number of late jobs with interval due-date uncertainty (Drwal 2017(Drwal , 2018.…”
Section: Maximum Regret Subproblemmentioning
confidence: 99%
“…We have also shown that there may exist infinitely many worst-case scenarios. Another example of a min-max regret scheduling problem with the property that worst-case scenario is not always extreme is the minimization of the weighted number of late jobs with interval due-date uncertainty (Drwal 2017(Drwal , 2018.…”
Section: Maximum Regret Subproblemmentioning
confidence: 99%